Factors affecting the length of stay in the intensive care unit of surviving infants with very low birth weight: A cross-sectional study - Myeryekye Amantai; Metin Dincer (Medicine Science, 2022)
Low birth weight causing mortality, morbidity, and lifelong disability is an important public health problem. Infants with very low birth have long hospital lengths of stay. The study aims to determine the factors affecting the length of stay of very low birth weight ( [Med-Science 2022; 11(1.000): 354-60]